Coordination and cooperation problems in network good production - Antonie Knigge; Vincent Buskens (Games, 2010)
If actors want to reach a particular goal, they are often better off forming collaborative relations and investing together rather than investing separately. We study the coordination and cooperation problems that might hinder successful collaboration in a dynamic network setting. We develop an experiment in which coordination problems are mainly due to finding partners for collaboration, while cooperation problems arise at the investment levels of partners who have already agreed to collaborate. The results show that as costs of forming links increase, groups succeed less often in solving the coordination problem. Still, if subjects are able to solve the coordination problem, they invest in a suboptimal way in the network good. It is mostly found that if cooperation is successful in terms of investment, it is due to subjects being able to monitor how much their partners invest. Moreover, subjects deal better with the coordination and cooperation problems as they gain experience.
Keywords: 330; network formation; coordination; cooperation; experiments; collective goods